Measuring Infant Visual Acuity with Gaze Tracker Monitored Visual Fixation. Issue 7 (July 2015) - Hathibelagal, Amithavikram R.; Leat, Susan J.; Irving, Elizabeth L.; Nandakumar, Krithika; Eizenman, Moshe
ABSTRACT Purpose To validate a method of measuring grating acuity with remote gaze tracking (GT) against a current clinical test of visual acuity (VA), the Teller Acuity Cards (TACs), as part of the development of an automated VA test for infants. Methods Visual acuity for computer-generated horizontal square-wave gratings was determined from relative fixation time on a grating area compared with the background. In experiment 1, binocular VA was based on eye movements with a GT in 15 uncorrected myopic adults and compared with VA measured with subjective responses with the same stimuli and with the TACs. In experiment 2, binocular VA was determined in 19 typically developing infants aged 3 to 11 months on two visits with both the GT and TACs. Results In adults, the mean difference between VA measured by the GT and TACs was 0.01 log cycles per degree (cpd) and the 95% limits of agreement were 0.11. One hundred percent of GT VA results were within 0.5 octave of the TACs' VAs. The mean difference between the GT and TACs for infants was 0.17 log cpd on both the first and second visit (95% limits of agreement, 0.42 and 0.47, respectively). The mean difference between test and retest for infant GT VA was 0.06 log cpd, and limits of agreement for repeatability were 0.48 log cpd. In infants, both the TACs and the GT had a reliability of 89% within less than or equal to 1 octave between visits. Gaze tracking VA improved with age and is in agreement with published norms. Conclusions The agreement between the TACs and GT in adults and infants validates the method of measuring grating acuity with the remote GT. These results demonstrate its potential for an automated test of infant VA.